The place of religion in education from the stand-point of Roman Catholicism - Alfons Paul Prinz (Centre for Educational Research, 2024)
Men everywhere are becoming aware o~ the powerlessness o~ modern education to produce Christians. Our children are no longer educated, in the sense attached to the word education in former times, but simply prepared for living in a secular sense. While some are quite contented and a sk no more than this o~ e ducation, others maintain that education should also include the culture o~ the soul. (b) The Church o~ Rome has always maintained the religious principle in education. It has there~ore a special right to speak on "Religion in Education". The approach to the problem in this thesis is made ~rom the Roman Catholic standpoint, and the ~i~th chapter is entirely devoted to Catholic Education, in order to illustrate that it is possible to combine the religious and the secular elements into one, viz. Christian education. In the ~irst two chapters the tripartite psychology o~ man, stipulating a body, a mind, and a soul, and the sultures corresponding to these parts o~ man, physical, mental, and spiritual, are dealt with. The next two chapters attempt to outline the present-day situation and to point out how this situation -2- was brought about. Having thus shown what should be done and what is actually being done to-day, I have then ventured, in the last three chapters, to make some positive suggestions as to what can be done, even when the environmental influences are by no means favourable. I wish to express my gratitude to Professors W.F. Grant and A.H. Murray for the very valuable assistance they have given me in the compilation of the thesis.